Analisis Beban Kerja dalam Meningkatkan Kinerja Karyawan pada PT XYZ Indonesia di Kota Tangerang - Salvia Mahmuda Ghaly; Rini Septiowati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze workload in improving employee performance at PT XYZ Indonesia in Tangerang City. Two core informants and five key informants met the sample criteria. The method used was a qualitative descriptive phenomenological approach with data collection techniques through observation, in-depth interviews, documentation of company management, NVivo, triangulation, and SWOT analysis. The results of this study indicate that PT XYZ Indonesia's workload is managed flexibly through setting targets based on Key Performance Indicators (KPIs) tailored to the capabilities of each employee. The work environment, both physical and non-physical, significantly influences work effectiveness and comfort. Some employees experience fatigue, especially when the workload increases, but the company provides compensation such as workload adjustments and work from home. The main obstacles in achieving targets are mostly caused by external factors such as client demands, the amount of work piling up, and limited work equipment. All employees follow clear Standard Operating Procedures (SOPs), and evaluations are conducted periodically to ensure the quality and quantity of performance are maintained. This research is expected to serve as a reference for companies in managing workloads and increasing employee productivity in the digital age.